2020
DOI: 10.1183/13993003.02135-2019
|View full text |Cite
|
Sign up to set email alerts
|

Pleuroparenchymal fibroelastosis in systemic sclerosis: prevalence and prognostic impact

Abstract: Interstitial lung disease (ILD) in systemic sclerosis (SSc) is a major cause of morbidity and mortality, mostly presenting as non-specific interstitial pneumonia. Little is known about the prevalence of pleuroparenchymal fibroelastosis (PPFE), a specific entity affecting the visceral pleura and subpleural parenchyma. We set out to estimate PPFE prevalence in two large cohorts of SSc patients and to assess its impact on survival and functional decline.A total of 359 SSc patients, derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 25 publications
4
44
0
1
Order By: Relevance
“…The study findings confirm observations in patients with scleroderma and chronic HP that demonstrated worsened survival with the presence of PPFE [7,8]. However, in neither study was PPFE associated with accelerated FVC decline.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The study findings confirm observations in patients with scleroderma and chronic HP that demonstrated worsened survival with the presence of PPFE [7,8]. However, in neither study was PPFE associated with accelerated FVC decline.…”
Section: Discussionsupporting
confidence: 87%
“…Visual PPFE was defined as pleurally-based triangular dense opacities (Fig. 2), occurring caudal to the upper 0.5 cm of the lung apices as per previous definitions [7,8]. Visual PPFE was quantified on a…”
Section: Ppfe Evaluation On Ctmentioning
confidence: 99%
“…PPFE accompanied with MAC-PD is a risk factor for lower BMI. Although weight loss and low BMI were reported in idiopathic PPFE and in the disease secondary to systemic sclerosis and idiopathic pulmonary fibrosis [11,13,24], no study has yet reported on the clinical impact of PPFE on BMI in patients with PPFE associated with MAC-PD. Consistent with other studies of secondary PPFE, the present study demonstrated that patients with MAC-PD and PPFE had a lower BMI (Tables 2 and 3).…”
Section: Discussionmentioning
confidence: 99%
“…PPFE is a specific clinical-pathological entity that Amitani et al and Frankel et al first reported [8,9]. Its pathogenesis remains unclear, but earlier studies reported that PPFE was associated with a variety of diseases, including autoimmune diseases, aspergillosis and NTM infection [7,[10][11][12][13]. Moreover, patients with PPFE and granulomatous diseases, including aspergillosis and MAC infection, had a better prognosis than those with PPFE without granulomas [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation